Frequency of In-Hospital Mortality among Patients of Severe Adult Tetanus Presenting with Bad Prognostic Factors - Khan, Hassan; Mashal; Malook, Said; Khan, Shuaib; Ali, Noor (Indus Journal of Bioscience Research, 2025)
Background: This investigation seeks to evaluate the in-hospital mortality rate of adult patients with severe tetanus who present with poor prognostic factors. No studies have been performed on this specific demographic in our region which makes the results of this investigation vital to supporting future research and optimizing the care frameworks for patients suffering from severe tetanus inappropriately advanced. These findings will be disseminated to public healthcare practitioners along with other medical professionals to inform them of the prevailing mortality figures and the need to enhance management, control, and preventative strategies for patients enduring severe tetanus. This study seeks to evaluate the mortality rate of patients with severe adult tetanus and poor pre-determined indicators of prognosis. Methodology: A descriptive cross-sectional study was conducted at the Department of Emergency Medicine, Lady Reading Hospital, Peshawar from 12th November 2023 to 12th May 2024. A total of 176 patients between the ages of 18 and 60 years with severe tetanus and noted poor prognostic factors were selected for the study. Every patient was managed as per existing protocols and the mortality during hospitalization was noted. The analysis was carried out on SPSS version 25. Results: The research had 176 participants aged between 18 and 60 years. Average age of participants was 38.54 years (standard deviation of 10.82), with body mass index (BMI) averaging at 24.08 (standard deviation of 1.73) kg/m². Mortality within the hospital was noted for 64 patients (36.4%). Conclusion: Patients with severe tetanus who have poor prognostic signs, for example, advance age or higher risk of sepsis, are still at a greater risk of in-hospital mortality, emphasizing the fact that more clinical attention is required with these patients and requires more prompt and effective treatment plans tailored to them.